Breeding and milking management practices of dairy animals in coastal areas of Gujarat (Indian Journal of Animal Production and Management, 2017)
A field survey was conducted during years 2010-2012 in Jalalpore taluka of Navsari district to ascertain  the breeding and milking management practices followed by dairy animal owners and data were collected  from randomly selected 150 dairy animal owners through personal interview with the help of pre-tested  structured schedule. The present study revealed that all the respondents detected heat in their animals  by observing the symptom of bellowing and mucous discharge (98%) and bred their animals by artificial  insemination (59.33%) between 12-18 hours after heat detection (46%). The 74.67% respondents bred  their animals after 5 months of calving and 27.33% respondents followed the pregnancy diagnosis by  veterinarian after 3 months of breeding. All the respondents washed their hands before milking and cleaned  teats and udder by splashing of water and milked their animals at same place twice in a day by adopting  wet hand (75.33%) and knuckling (69.33%) methods of milking. Majority (74.67%) of respondents allowed  calves for suckling before milking for letdown of milk and 98% of respondents did not follow teat dipping  after milking. Only 2% of respondents followed testing for mastitis in their dairy animals. The 44 and 56%  respondents adopted practice of drying off their dairy animals for less than two months and two months/ more time before calving, respectively. Majority (90%) of respondents sold their milk to village dairy co
Keywords: Breeding; Dairy animals; Management; Milking practices